Faktor Sosiodemografi dan Self Efficacy Penderita Diabetes Mellitus Tipe 2 (Study pada Peserta Prolanis) di Puskesmas Talaga Bodas Bandung - Salami Salami (Jurnal Medika Cendikia, 2017)
In Indonesia the number of patients with DM Type 2 disease is increasing, based on Blueprint for Change report released in September 2013 it is known that the number of DM patients amounted to 7.6 million people. The number of DM patients in Indonesia rose from rank 9 to rank 7 countries in the world. The number of DM patients receiving treatment was only 39 percent, and only 0.7 percent achieved treatment targets. The success of treatment is influenced by various factors such as self efficacy. Self efficacy is one of the important factors in the management of type 2 diabetes. High self efficacy is related to the improvement of glycemic control, medication compliance and self management. The sociodemographic factor is an important factor that must be known to encourage a person to behave in a belief in controlling his illness. This study aims to determine the relationship between sociodemographic factors with self efficacy of type 2 diabetes mellitus. This type of research is descriptive correlation with cross sectional approach. The number of samples used is simple random sampling as much as 40 respondents of prolanis participants at Talaga Bodas Health Center Bandung by using questionnaires Diabetes Self-Efficacy Questionnare (DSEQ). Based on bivariate analysis, there was no correlation between age, sex, occupation and income ( significant between education, duration of illness with self efficacy (p <0,05) relation between age and self efficacy (p value = 0,224). Gender variable, it is known that women have good self efficacy that is equal to 91,6% while efficacy less 8,4% Based on bivariate analysis there is no relationship between sex with self efficacy (p value = 0,102) Similarly, job = 0,916) and income (p value = 0,132), and history of care (p value 0,132), whereas based on educational level and length of DM disease there is correlation with (p value = 0,003) and (p value = 0,001).